Sei sulla pagina 1di 4

# Exercise 3.

2 (Solutions)

mathcity.org

## Available online @ http://www.mathcity.org, Version: 1.0.4

Theorem on Anti-Derivatives
i) cf ( x) dx = c f ( x) dx where c is constant.
ii)

= x 2 dx + x dx
3

## [ f ( x) g ( x)] dx = f ( x)dx g ( x)dx

Important Integral
d n+1
Since
x = ( n + 1) x n
dx
Taking integral w.r.t x
d n +1
n
dx x dx = ( n + 1) x dx
x n+1 = ( n + 1) x n dx

n
x dx =

x n +1
n +1

where n -1

If n = -1 then
1
dx = dx
x
d
1
Since
ln x =
dx
x
1
Therefore dx = ln x + c
x
Note: Since log of negative numbers does not
exist therefore in above formula mod assure that
we are taking a log of +ive quantity.

Important Integral
n +1
n
d
ax + b ) = ( n + 1) ( ax + b ) a
Since
(
dx
Taking integral
n +1
n
d
dx ( ax + b ) dx = (n + 1) ( ax + b ) a dx
n +1
n
( ax + b ) = ( n + 1) a ( ax + b ) dx

-1

( ax + b )

( 2 x + 3)

dx

Question # 1(v)

+1

x1+1
x2
=
+2
+ x+c
1+1
1
+1
2
3

x2
x2
= +2
+ x+c
2
3
2

1
x + 1 dx = x x 2 + 1 dx

= x 2 + x dx

= x dx + 2 ( x ) 2 dx + dx

1
- +1
2

Question # 1(iii)

= x + 2 ( x ) 2 + 1 dx

x
x
+
+c
1
1
+1 - +1
2
2
3

+c

x + 1 dx = ( x ) 2 + 2 x + 1 dx

x2 x2
=
+
+c
3
1
2
2
1
2 32
= x + 2 x 2 + c Ans.
3

1 + 1 2
2

3 2
2

3
1
= ( 2 x + 3) 2 + c
3

= x 2 dx + x 2 dx
1
+1
2

+1

Question # 1(ii)
1
-
12

1
2 dx
x
+
dx
=
x
+
x

( 2 x + 3) 2
=

( 2 x + 3) 2 + c
=

= 3

n +1

(n + 1) a

1
2

x 2 +1
x1+1
- 2
+ x+c
2 +1
1+1
x3
x2
= 3 - 2 + x + c
3
2
3
2
= x - x + x+c

( ax + b )
dx =

Question # 1(iv)

Question # 1(i)
2
2
3x - 2 x + 1 dx = 3 x dx - 2 xdx + dx

+1

x2
x1+1
x 2 x2
=
+
+c =
+ +c
3
1+1
5
2
+1
2
2
2 52 1 2
= x + x +c
5
2

x2 4 x 2
= +
+ x+c
2
3
Question # 1(vi)
2

1
1

x - x dx = x + x - 2 dx
1
= xdx + dx - 2 dx
x
2
x
=
+ ln x - 2 x + c
2

## FSc-II / Ex- 3.2 - 2

Question # 1(vii)
3x + 2
3x + 2
x dx = x1 2 dx
3x
2
= 1 2 + 1 2 dx
x
x
12
= 3x + 2 x -1 2 dx

= e x dx + dx
= ex + x + c

Question # 2(i)
dx
x+a + x+b
dx
x+a - x+b
=

## x+a + x+b x+a - x+b

x+a - x+b
=
dx
x+a- x-b

= 3 x1 2 dx + 2 x -1 2 dx

Now do yourself.
Question # 1(viii)
y ( y + 1)
y dy
y ( y + 1)

( y)

dy =

( y + 1) dy

1
y
-
1
1
=
+
dy = y 2 + y 2 dy

y
y

1
- +1

= y 2 dy + y 2 dy
+1

y2
y 2
y2 y2
=
+
+c =
+
+c
1
1
3
1
+1 - +1
2
2
2
2
1
2 32
= y + 2y2 + c
3
Question # 1(ix)

q -1

dq =

(q - 2

) dq

q +1
q

q
2 q
1
=
+
dq
q
q
q

1
1

= q 2 - 2 + q 2 dq

No do yourself
Question # 1(x)
Do yourself as above
Important Integral
d ax
We know
e = a eax
dx
Taking integral
d ax
ax
dx e dx = a e dx
e ax = a eax dx

ax
e dx =

## Also note that

e ax
a

( ax + b )
e dx =

e( ax +b )
a

Question # 1(xi)
e 2x e x
e 2x + e x
dx
=
ex
e x + e x dx
= e x + 1 dx

Ans

( x + a)2 - ( x + b)2
a -b

dx

1
1
1

2 dx - ( x + b ) 2 dx
x
+
a
(
)

a - b

1
1

+1
x + b)2
(
1 ( x + a )2
=
+c
a -b 1
1
+
1
+
1
2

2
3
3

1 ( x + a ) 2 ( x + b) 2
=
+c
a -b 3
3
2
2

3
3
2

2 - ( x + b ) 2 + c Ans.
x
+
a
(
)

3( a - b)

Important Integral
d
1
Tan -1 x =
Since
dx
1 + x2
d
1
Also
- Cot -1 x =
dx
1 + x2
1
Therefore
dx = Tan -1 x or - Cot -1 x
2
1+ x
1
Similarly
dx = Sin -1 x or - Cos -1 x
2
1- x
1
-1
-1
x x2 - 1 dx = Sec x or - Csc x

Question # 2(ii)
1 - x2
1 + x 2 dx
2

= -1 +
dx
1 + x2

1
= - dx + 2
dx
1 + x2
= - x + 2Tan -1 x + c

-1
1 + x 1 - x2

Question # 2(iii)
dx
x+a + x
dx
x+a - x
=

x+a + x x+a - x
x+a - x
=
dx
x+a-x
1

( x + a)2 - ( x)2
a

dx

-1 - x 2
+

## FSc-II / Ex- 3.2 - 3

1
1
1

2
x
+
a
dx
x
(
)
( ) 2 dx
a

sec ax tan ax dx =

1
1

+1
x)2
(
1 ( x + a)2
=
+c
a
1
1
1
1
+
+
2
2
3
3

1 ( x + a)2 ( x)2
=
+c
a
3
3
2
2

csc ax cot ax dx = -

cos ( ax + b )
a
sin ( ax + b )
and so on.
cos ( ax + b ) dx =
a

## sin ( ax + b ) dx = Question # 2(vi)

sin(a + b) x dx = -

Question # 2(iv)
3

( a - 2 x ) dx =

( a - 2x)2

+c

= 2sin 2 x dx

( a - 2x)2
=

Question # 2(v)
x 3

dx =

(1 + 3e

+ 3e 2 x + e3 x
e

) dx

1 3e 3e 2 x e3 x
= x + x + x + x
e
e
e
e
-x
x
2x
= e + 3 + 3e + e dx
x

-x

dx

Important Integrals
d
cos ax = - a sin ax
We know
dx
Taking integral
d
dx cos ax dx = - a sin ax dx
cos ax = - a sin ax dx

sin ax dx = -

cos ax
a

d
sin ax = a cos ax
dx
sin ax
\ cos ax dx =
a
Similarly
tan ax
2
sec ax dx = a
Also

cosec

Important Formula
n +1
n d
d
Q
f ( x)
[ f ( x)] = ( n + 1) [ f ( x)] dx
dx
n +1
n
d

f ( x )] = ( n + 1) [ f ( x )] f ( x )
[
dx
Taking integral
n +1
n
d
dx [ f ( x)] dx = ( n + 1) [ f ( x)] f ( x)dx
n +1
n
[ f ( x )] = ( n + 1) [ f ( x )] f ( x )dx

ax dx = -

cot ax
a

[ f ( x)]
[ f ( x)] f ( x)dx = ( n + 1)

n +1

2x

e
e
+ 3x + 3e x +
+c
-1
2
1
= -e- x + 3 x + 3e x + e2 x + c
2
=

1 - cos 2 x
2

= - 2 cos x + c

( a - 2x)2 + c
=-

(1 + e )

Q sin 2 x =

= 2 sin x dx = 2 ( - cos x ) + c

+c

5
2 ( -2 )

cos(a + b) x
a+b

Question # 2(vii)
1 - cos 2x dx

+1

3 + 1 -2
2 ( )

csc ax
a

## Also note that

3
3

2
2 - x 2 + c Ans.
x
+
a
(
)

3a

3
2

sec ax
a

; n -1

d
1
ln f ( x) =
f ( x )
dx
f ( x)
Taking integral
f ( x )
ln f ( x) =
dx
f ( x)
Also

i.e.

f ( x )
dx = ln f ( x) + c
f ( x)

Question # 2(viii)
1
Let I = ln x dx
x
Put f ( x ) = ln x f ( x) =
So I = [ f ( x)] f ( x ) dx

[ f ( x)]
=

1+1

+c
1+1
2
ln x )
(
=
+c
2

1
x

[ f ( x)]
=

+c

## FSc-II / Ex- 3.2 - 4

Question # 2(ix)
1 - cos 2 x
2
sin x dx = 2 dx
1 1

= - cos 2 x dx
2
2

1
1
= dx - cos 2 x dx
2
2
1
1 sin 2 x
= x+c
2
2 2
1
1
= x - sin 2 x + c
2
4
Question # 3(x)
1
1 + cos x dx
1
=
dx
2 x
2 cos
2
x
1
= sec2 dx
2
2

Q cos 2

x 1 + cos x
=
2
2

x
x
1 tan 2
=
+ c = tan + c
2 1
2
2

Alternative
1
1
1 - cos x
1 + cos x dx = 1 + cos x 1 - cos x dx
1 - cos x
dx
=
1 - cos 2 x
1 - cos x
=
dx
sin 2 x
cos x
1
= 2 - 2 dx
sin x sin x
cos x

= cosec2 x dx
sin x sin x

## = cosec2 xdx - cosec x cot x dx

= - cot x - ( - cosec x ) + c
= cosec x - cot x + c

Question # 2(xi)
ax + b
Let I = 2
dx
ax + bx + c
Put f ( x ) = ax 2 + 2bx + c
f ( x) = 2ax + 2b
f ( x ) = 2 ( ax + b )

1
f ( x ) = ax + b
2

1 f ( x )
So I = 2
dx
f ( x)
1
1 f ( x )
=
dx = ln f ( x) + c1
2 f ( x)
2
1
= ln ax 2 + bx + c + c1
2

Review
2sin a cos b = sin (a + b ) + sin (a - b )
2 cos a sin b = sin (a + b ) - sin (a - b )
2 cos a cos b = cos (a + b ) + cos (a - b )
- 2sin a sin b = cos (a + b ) - cos (a - b )

Question # 2(xii)
cos 3x sin 2 x dx
1
2 cos 3x sin 2 x dx
2
1
= [sin(3 x + 2 x) - sin(3 x - 2 x)] dx
2
1
= [sin 5 x - sin x ] dx
2
1 cos 5 x

= - ( - cos x ) + c
2
5

1 cos 5 x

=-
- cos x + c
2 5

Question # 2(xiii)
cos 2 x - 1
1 - cos 2 x
Q sin 2 x =
1 + cos 2 x dx
2
1 + cos 2 x
2
1 - cos 2 x
cos x =
= -
dx
2
1 + cos 2 x
2
2sin x
= -
dx
2 cos 2 x
= - tan 2 x dx = - sec 2 x - 1 dx

= - sec 2 x dx + dx
= - tan x + x + c

Question # 2(xiv)
2
2
tan x dx = sec x - 1 dx

= sec2 x dx - dx
= tan x - x + c

Important Integral
d
1
d
Since
ln ax + b =
( ax + b )
dx
ax + b dx
d
1

ln ax + b =
a
dx
ax + b
On Integrating
1
ln ax + b = a
dx
ax + b
ln ax + b
1

dx =
ax + b
a
The End
Thursday, 11 November 2012
By mathcity.org, mathcity@gmail.com
Found Error
Tell us at
http://www.mathcity.org/error
Error Analysts
1-

PISH AL-HASA KSA